2011
DOI: 10.1007/s00520-011-1172-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of cancer needs questionnaire for parents and carers of adolescents and young adults with cancer

Abstract: The questionnaire developed has demonstrable face and content validity and acceptability. Unmet needs are prevalent among parents and carers of AYA cancer survivors, suggesting the need for further psychometric testing of the measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…One study found that 28%–36% of the parents and other caregivers of AYAs with cancer had a high or very high level of unmet needs, particularly related to information about the long-term effects of treatment and the young person's fertility. 9 In another study, similar findings were found. 10 The parents of AYAs with cancer had a high level of unmet need for information.…”
Section: Introductionsupporting
confidence: 71%
“…One study found that 28%–36% of the parents and other caregivers of AYAs with cancer had a high or very high level of unmet needs, particularly related to information about the long-term effects of treatment and the young person's fertility. 9 In another study, similar findings were found. 10 The parents of AYAs with cancer had a high level of unmet need for information.…”
Section: Introductionsupporting
confidence: 71%
“…They reported that parents had information needs especially on fertility and post‐treatment challenges and the desire to receive the information in a written format, like an information booklet. Other studies assessed needs in a broader way and found that information need was the most prevalent unmet need .…”
Section: Discussionmentioning
confidence: 99%
“…Unmet cancer-related needs. We used a subset of 17 items from the Cancer Needs Questionnaire for Parents/Carers of Adolescents and Young Adults with Cancer [ 62 ] to gauge support person unmet needs over time.…”
Section: Methodsmentioning
confidence: 99%